1998
DOI: 10.1590/s0301-80591998000100009
|View full text |Cite
|
Sign up to set email alerts
|

Influência da temperatura no desenvolvimento de Euborellia annulipes (Lucas) (Dermaptera: Anisolabididae), predador do bicudo-do-algodoeiro

Abstract: Influence of Temperature on the Development of Euborellia annulipes (Lucas)(Dermaptera: Anisolabididae), Predator of Cotton Boll Weevil ABSTRACT -The biology and influence of temperature on the development of nymphal stages of Euborellia annulipes (Lucas) was studied in growth chambers at 15, 20, 23, 25, 28, 30, 33, and 35°C, 60 ± 10% RH, and 14L:10D photoperiod. The viability of eggs ranged from 72.5% (20°C) to 89.3% (28°C).Temperatures of 15° and 35°C were lethal to eggs. The egg incubation period ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 8 publications
1
9
0
8
Order By: Relevance
“…According to this author, eggs do not develop at 10 and 14ЊC; however, a high proportion of eggs hatch at 20ЊC (73.6%) and 32ЊC (85.4%). Lemos et al (1998) reported that this predator had egg survival of 85.5% (at 25ЊC) and 78.1% (at 30ЊC), which are similar to the survival rates obtained in this research. These rates varied greatly as a function of the age of females at both temperatures.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…According to this author, eggs do not develop at 10 and 14ЊC; however, a high proportion of eggs hatch at 20ЊC (73.6%) and 32ЊC (85.4%). Lemos et al (1998) reported that this predator had egg survival of 85.5% (at 25ЊC) and 78.1% (at 30ЊC), which are similar to the survival rates obtained in this research. These rates varied greatly as a function of the age of females at both temperatures.…”
Section: Resultssupporting
confidence: 89%
“…The ringlegged earwig Euborellia annulipes (Lucas) has been reported as an efÞcient natural enemy of Cosmopolites sordidus German (Curculionidae) and some pest insects of stored grains (Klostermeyer 1942), as well as lepidopterous pests in sugar-cane ecosystems in the United States and Japan (Klostermeyer 1942, Gould 1948, Hensley 1971. Recently, studies conducted by Ramalho and Wanderley (1996), and Lemos et al (1998Lemos et al ( , 1999 reported the possibility of using E. annulipes as a predator of larvae and pupae of the cotton boll weevil in the northeast region of Brazil.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nas demais temperaturas, a viabilidade dos ovos foi superior a 84%, para D. luteipes, e para D. lineare houve um decréscimo nas temperaturas extremas, e a temperatura de 25ºC foi a mais favorável (Tabela 1). Semelhante ao observado neste trabalho, LEMOS et al (1998) também observaram que temperaturas de 15 e 33ºC desfavorecem o desenvolvimento embrionário de Euborellia annulipes (Lucas) (Dermaptera: Anisolabididae), ou seja, há uma tendência de que as temperaturas na faixa de 18 a 28ºC sejam as ideais pa ra o desenvolvimento embrionário de dermápteros (SHEPARD et al, 1973; JONES et al, 1988; JAMET & CAUSSANEL, 1995;LEMOS et al, 1998), o que está de acordo com a faixa de temperatura encontrada para D. luteipes e D. lineare neste trabalho.A temperatura promoveu variações na duração dos ínstares para ambas as espécies, com diferenças significativas para o desenvolvimento ninfal. Entretanto, o número de ínstares foi constante (4), independente da temperatura, para ambas as espécies.…”
unclassified
“…The colonies of the ringlegged earwigs were established in the Biological Control Unity of the Embrapa Algodão, Campina Grande, Para ıba, Brazil (Lemos et al, 1998) and, posteriorly, reared at LEN/UFPB, and they were supplemented with field-collected individuals every 2-3 years. The colonies of the ringlegged earwigs were established in the Biological Control Unity of the Embrapa Algodão, Campina Grande, Para ıba, Brazil (Lemos et al, 1998) and, posteriorly, reared at LEN/UFPB, and they were supplemented with field-collected individuals every 2-3 years.…”
Section: Predator and Prey Rearingmentioning
confidence: 99%